BIOSORPSI ION LOGAM Cr(VI) DENGAN MENGGUNAKAN BIOMASSA LAMUN Enhalus acoroides YANG TERDAPAT DI PULAU BARRANG LOMPO - Nursiah La Nafie; Paulina Taba; Djasmawati Mahmud (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2009)
Biosorption is an alternative technique which can be used in solving environmental  pollution coming from waste containing heavy metals. Biosorption  of Cr(VI) ion using biomass of seagrass,  Thalassia hemprichii at various contact time, pH and concentration has been investigated. Biosorption was performed by a batch method and  concentration  of  ions  before  and  after  biosorption  were  measured  by  atomic absorption spectrophotometer  (AAS). The equilibrium was achieved after 80 minutes. Adsorption  effectivity  of  Cr(VI)  Enhalus  acoroides  ion  was  pH  2.  Biosorption  of Cr(VI) ion by using biomass of Enhalus acoroides followed Langmuir isotherm and the result showed that biosorption capacity (Qo) of Cr(VI) ion was 8.13 mg/g.Keywords:  biosorption, Cr(VI), seagrass, Enhalus acoroides, Langmuir isotherm.